Management Controlling of Progamme Desa Mandiri Cinta Petani in Timor Tengah Utara Regency - Sulistio Diliwanto Binsasi; Endang Larasati; Ida Hayu Dwimawanti (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
Management controlling is a important role in the implementation of a program, because this function has a role to measure the suitability of activities with a predetermined plan. The purpose of this study was to analyze and describe the supervisory function in the management of the independent love village farmers program (Sari Tani) in Timor Tengah Utara Regency. The formulation of the problem in this study is how the supervision function of the farmer sari program in Timor Tengah Utara Regency. To answer these problems, the management is used which has relevance to the phenomenon of research. This research is a qualitative research with Milles and Huberman data analysis techniques. The results of the study showed that control in the program management of the independent love villages of farmers in Timor Tengah Utara Regency was not yet in line with the technical guidelines. As a result of the large amount of arrears on farmer sari refunds and the jamming of the farmers' funds, due to lack of awareness of beneficiaries who do not want to return Fund of sari tani programs (DST),  Sari Tani Programe management unit (UPST) administrators do not comply with regulations relating to DST rolling procedures, and there is no direct action or direct affirmation to beneficiaries who have not repaid the refund of the farmer's juice.